Isolation and characterization of an olfactory receptor protein for odorant pyrazines. - Pevsner, J (1985)
The highly potent bell pepper odorant 2-isobutyl-3-[3H]methoxypyrazine [( 3H]IBMP) binds specifically and saturably to bovine and rat nasal epithelium. Specific binding is not detected in 11 other tissues assayed, and in the rat binding is 9 times higher in olfactory than in respiratory epithelium. We have purified to apparent homogeneity a soluble pyrazine odorant binding protein that constitutes approximately equal to 1% of the total soluble protein in bovine nasal epithelium. Polyacrylamide gel electrophoresis shows a single band of 19,000 Da and gel filtration data suggest that the native protein is a dimer of 38,000 Da. Binding of [3H]IBMP to the purified protein reveals two binding sites (Kd = 10 X 10(-9) M, Bmax = 135 pmol per mg of protein; Kd = 3 X 10(-6) M, Bmax = 25 nmol per mg of protein). The binding affinities of a homologous series of pyrazine odorants correlate with the human odor detection thresholds of these compounds. This correlation, together with the regional distribution of the protein, suggests that the protein is a physiologically relevant olfactory receptor.